Bamboo grid versus polyvinyl chloride as packing material in cooling tower: Energy efficiency and environmental impact assessment. (15th May 2021) - Ma, Xinxin; Cai, Liping; Chen, Lisheng; Fei, Benhua; Lu, Jiping; Xia, Changlei; Lam, Su Shiung
Abstract: As an abundant and fast-growing biomass, bamboo can be used as construction materials owing to its desirable physical and mechanical properties, environmentally friendly features, and alternative to replace toxic and hazardous wastes in industrial processing. In this study, grid material made from bamboo (termed 'bamboo grid') was developed and compared to commercially used polyvinyl chloride (PVC) as packing material in cooling towers; PVC packing has drawbacks such as fouling, deposit buildup, low durability, and is harmful to environments. The cooling capacity, energy efficiency and environmental impact of bamboo grid packing were evaluated via life cycle assessment (LCA), particularly the cumulative energy demand (CED) and the Building for Environmental and Economic Sustainability (BEES). Although the thermal performance of the PVC packing was found higher than that of the bamboo grid packing, the bamboo grid packing showed improved resistance characteristic, recording a total saving of 529.2 tons of standard coal during a six-month field test in a real thermal power generation plant. LCA results revealed that the utilization of bamboo-grid packing to replace PVC packing in cooling towers reduced total CED from 3420 MJ to 561 MJ per functional unit, achieving 6 times reduction. A desirable reduction ranging from 1.5 to 10.5 times was also recorded for the BEES indices. This LCA comparison analysis confirmed the improvement of energy efficiency and reduction of environmental impact by using the bamboo grid to replace PVC as packing material in cooling towers. The major environmental impact (BEES) indices (e.g., the total Global warming potential, Acidification, Eutrophication and Smog) were reduced by 1.5–10.5 times via the use of bamboo grid. The results demonstrate that bamboo grid packing is a good alternative to replace existing grid packing materials such as concrete and PVC that are harmful to human health and environments. Graphical abstract: Image 1 Highlights: Bamboo is a potential cooling packing material used in power plants. Bamboo grid packing has better cooling capacity than conventional polymer packing. Energy efficiency and environmental impact are evaluated via life cycle assessment. Cumulative demand reduces from 3420 to 561 MJ per functional unit.